Effects of alcohol concentration and temperature on the dynamics and stability of mutant Staphylococcal lipase - Ong, Shir Nee; Ahmad Kamarudin, Nor Hafizah; Mohd Shariff, Fairolniza; Muhd Noor, Noor Dina; Mohamad Ali, Mohd Shukuri; Raja Abd. Rahman, Raja Noor Zaliha (Informa UK Limited, 2023)
The stability and activity of lipase in organic media are important parameters in determining how quickly biocatalysis proceeds. This study aimed to examine the effects of two commonly used alcohols in industrial applications, methanol (MtOH) and ethanol (EtOH) on the conformational stability and catalytic activity of G210C lipase, a laboratory-evolved mutant of Staphylococcus epidermidis AT2 lipase. Simulation studies were performed using an open-form predicted structure under 30, 40 and 50 of MtOH and EtOH at 25‰°C and 45‰°C. The overall enzyme structure becomes more flexible with increasing concentration of MtOH and exhibited the highest flexibility in 40 EtOH. In EtOH, the movement of the lid was found to be temperature-dependent with a noticeable shift in the lid position at 45‰°C. Lid opening was evidenced at 50 of MtOH and EtOH which was supported by the increase in SASA of hydrophobic residues of the lid and catalytic triad. The active site remained mostly intact. An open-closed lid transition was observed when the structure was re-simulated in water. Experimental evaluation of the lipase stability showed that the half-life reduced when the enzyme was treated with 40 (v/v) and 50 (v/v) of EtOH and MtOH respectively. The finding implies that a high concentration of alcohol and elevated temperature can induce the lid opening of lipase which could be essential for the activation of the enzyme, provided that the catalytic performance in the active site is not compromised.